ACTR-25. RETHINKING THE DOGMA: HOW IMPORTANT IS TREATMENT OF THE CSF IN PATIENTS WITH PRIMARY CNS LYMPHOMA (PCNSL)?. (11th November 2019) - Aregawi, Dawit; Korfel, Agnieszka; Schlegel, Uwe; Glantz, Michael
Abstract: INTRODUCTION: PCNSL constitutes a small but important fraction of adult malignant primary brain tumors. These tumors frequently and often dramatically respond to high-dose methotrexate-containing regimens, but almost inevitably recur. Following initial treatment and at the time of recurrence, no widely accepted treatment paradigm exists. In particular, no consensus exists regarding the need to treat the CSF at the time of PCNSL diagnosis. METHODS: We identified three independent cohorts of adults with PCNSL in which some patients received intra-CSF chemotherapy as part of their initial therapy, and others did not. All patients were comparable with respect to demographic and disease characteristics (study-level data). Data on CSF involvement, response, relapse, and survival were extracted and summary statistics were calculated from these three studies using the inverse variance method and random effects model. RESULTS: The three cohorts were treated with: HD MTX/rituximab/ifosfamide followed by either HD MTX/cytarabine/ifosfamide (group Ia), or cytarabine/thiotepa and autologous stem cell transplant (group Ib) (n=80); HDMTX/rituximab/vinca alkaloids/ifosfamide/cytarabine (group II) (n=48); or HD MTX/rituximab (group III). Intra-CSF chemotherapy consisted of MTX/cytarabine/prednisolone (group Ia only, n=43); MTX/cytarabine/prednisolone (group II, n=30); or liposomal cytarabine (group III, n=21). One- and two-year survivals were greater in the IT chemotherapy compared to the no-IT chemotherapy groups (RR 1.25 [1.16–1.34] and 1.20 [1.14–1.26] respectively, p< 0.001 for both). Relapse involving the CSF was greater in the non-IT chemotherapy group (RR 2.31 [2.03–2.62], p< 0.001). In one cohort, comparison of pre-treatment CSF cytology from ventricular vs lumbar sites was possible. CSF cytology was positive in 81% of ventricular specimens vs 14.3% of lumbar specimens (p< 0.0001). CONCLUSIONS: CSF involvement by tumor occurs in most patients with PCNSL. Including intra-CSF chemotherapy in the initial treatment regimen of these patients may improve overall survival and reduce the frequency of relapses involving the CSF. Well-designed prospective trials are warranted.